Examine the quality of translated Chinese picture books from an education perspective - Li, Liangli (Nanyang Technological University, 2022)
The quality of translated Chinese picture books in China varies which raises concern. Not enough attention is paid towards children’s picture books which are stereotyped as easy to translate. Limited research about Chinese translation of imported picture books for specific age level and how picture books’ translation impact and support children’s learning and development. This research aims to examine the quality of translated Chinese picture books from an education perspective. Lev Vygotsky’s sociocultural theory and whole language approach lay the education foundation for this research. The selected age level is 5-6 years old. According to children’s development patterns, children of 5 to 6 years old acquire language and reading skills through exposing to reading materials and adults’ direct instructions. Picture books as a type of prevalent reading resource for children, it can guide children to develop their literacy skills and imagination while reading. Two research questions are then posed: (1) Do the translated Chinese picture books support children’s literacy and critical thinking skills as the source texts (STs) do? (2) What characteristics of picture books have been translated in the Chinese translation to support children’s literacy and critical thinking? Two translated Chinese picture books are chosen from the suggested reading list published by Ministry of Education of People’s Republic of China to complete case studies for this qualitative research. A theoretical framework is formed based on picture books’ characteristics, concepts and translation studies and the two mentioned education theories to guide the case studies. This research finds out that translated Chinese picture books do support children’s literacy and critical thinking skills, but to what extent depends on the translation quality. Picture books’ characteristics of rhythmic text and reciprocity of text and illustrations support children’s literacy and critical thinking.